2018
DOI: 10.1186/s12968-018-0497-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired aortic distensibility and elevated central blood pressure in Turner Syndrome: a cardiovascular magnetic resonance study

Abstract: BackgroundWomen with Turner Syndrome have an increased risk for aortic dissection. Arterial stiffening is a risk factor for aortic dilatation and dissection. Here we investigate if arterial stiffening can be observed in Turner Syndrome patients and is an initial step in the development of aortic dilatation and subsequent dissection.MethodsFifty-seven women with Turner Syndrome (48 years [29–66]) and thirty-six age- and sex-matched controls (49 years [26–68]) were included. Distensibility, blood pressure, carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 54 publications
(65 reference statements)
0
14
0
Order By: Relevance
“…Coarctation is associated with an increased likelihood of aortic dilation and dissection (Bambul Heck, Pabst von Ohain, Kaemmerer, Ewert, & Hager, ; Cools, Brown, & Gewillig, ; Eckhauser et al, ). Hypertension, a common consequence of aortic coarctation that may manifest in childhood, and altered compliance or distensibility of the aorta, which is prevalent in patients with coarctation, may both contribute to aortic disease (Hjerrild et al, ; Pees et al, ; Schoepp et al, ; Wen et al, ). Re‐interventions due to re‐coarctation are often necessary in adulthood.…”
Section: Cardiovascular Health Issuesmentioning
confidence: 99%
“…Coarctation is associated with an increased likelihood of aortic dilation and dissection (Bambul Heck, Pabst von Ohain, Kaemmerer, Ewert, & Hager, ; Cools, Brown, & Gewillig, ; Eckhauser et al, ). Hypertension, a common consequence of aortic coarctation that may manifest in childhood, and altered compliance or distensibility of the aorta, which is prevalent in patients with coarctation, may both contribute to aortic disease (Hjerrild et al, ; Pees et al, ; Schoepp et al, ; Wen et al, ). Re‐interventions due to re‐coarctation are often necessary in adulthood.…”
Section: Cardiovascular Health Issuesmentioning
confidence: 99%
“…Although one study reported no association between BP and aortic growth during 2.4 years of follow‐up, several studies have reported hypertension to be an important and modifiable risk factor for aortic dilation . In particular, systolic BP was associated with aortic distensibility in patients with TS . According to the recent guideline for patients with TS, systolic hypertension is recommended as a target of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Women with Turner Syndrome are at increased risk for aortic dissection. Wen et al [84] explored arterial stiffness in 57 women with Turner Syndrome. They found Turner Syndrome was associated with descending aorta distensibility, primarily among those with aortic coarctation, with similar distensibility among Turner Syndrome patients without coarctation.…”
Section: Congenital Heart Diseasementioning
confidence: 99%